Produksi Enzim Lakase Oleh Jamur Trichoderma Asperelloides LBKURCC2 Menggunakan Substrat Jerami Padi Secara Fermentasi Kultur Padat Dengan Variasi Waktu Fermentasi Dan Laju Aerasi 1,5 L/M - Iwara, Bangkit Swadi; Helianty, Sri; Dahliaty, Andi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Laccase (benzenediol:oxygen oxidoreductase, EC 1.10.3.2) is classified as blue copper oxidase enzyme. Laccase generally found in plant, insect, bacteria and filamentous fungus. One of filamentous fungus that able to degradates lignin is Trichoderma. Lignin is available in biomass such as rice straw, that contains around 18% lignin. The technique of producing laccase enzymes in this study is solid state fermentation. Solid state fermentation allows microorganisms to grow in conditions close to or similar to their natural habitat, with relatively better product than submerged state fermentation. In this study, the effect of giving force aeration on variations in fermentation time was studied in order to obtain optimum conditions for the production of laccase enzyme by solid state fermentation using the fungus Trichoderma asperelloides LBKURCC2 with rice straw substrate on a tray bioreactor. The fermentation is carried out with variation of the fermentation time 6, 8, and 10 days with incubation temperature of 30 ± 2 ºC, acetate buffer solution pH 5.5 (0.05 M), substrate size 1 cm, addition of 0.5 g / l CuSO4.7H2O inducer, bed height 3 cm, and aeration rate 1.5 l / m. The highest laccase enzyme activity was obtained during the production time of 8 days, with an average 7.78 x 10-6 U / L. The 8th day is considered to be the best growth time where the enzyme activity has reached its peak and is in a stagnant condition after the increase that occurred on the 6th and 7th days. Meanwhile, on the 9th and 10th days there was a significant decrease in the activity of the laccase enzyme due to the greater repression of catabolites.Keywords: Laccase, Solid State Fermentation, Tray Bioreactor, Force Aeration, FermentationTime